Physical fitness of elite belgian soccer players by player position - Boone, J.; Vaeyens, R.; Steyaert, A.; Bossche, L. V.; Bourgois, J. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to gain an insight into the physical and physiological profile of elite Belgian soccer players with specific regard to the player's position on the field. The sample consisted of 289 adult players from 6 different first division teams. The players were divided into 5 subgroups (goalkeepers, center backs, full backs, midfielders, and strikers) according to their self-reported best position on the field. The subjects performed anaerobic (10-m sprint, 5 × 10-m shuttle run [SR], squat jump [SJ], and countermovement jump [CMJ]) and aerobic (incremental running protocol) laboratory tests. The strikers had significantly shorter sprinting times (5-, 5- to 10-m time, and SR) compared with the midfielders, center backs, and goalkeepers, whereas the full backs were also significantly faster compared with the goalkeepers and the center backs. The goalkeepers and the center backs displayed higher jumping heights (total mean SJ = 40.7 ± 4.6 cm and CMJ = 43.1 ± 4.9 cm) compared with the other 3 positions, whereas the strikers also jumped higher than the full backs and the midfielders did. Regarding the aerobic performance, both full backs and the midfielders (61.2 ± 2.7 and 60.4 ± 2.8 ml/min/kg, respectively) had a higher VO2max compared with the strikers, center backs, and goalkeepers (56.8 ± 3.1, 55.6 ± 3.5, and 52.1 ± 5.0 ml/min/kg, respectively). From this study, it could be concluded that players in different positions have different physiological characteristics. The results of this study might provide useful insights for individualized conditional training programs for soccer players. Aside from the predominant technical and tactical skills, a physical profile that is well adjusted to the position on the field might enhance game performance.